2011
DOI: 10.1007/s10531-011-0036-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rubber plantations on the diversity and activity of understorey insectivorous bats in southern Thailand

Abstract: Although a large proportion of tropical rain-forest in South-east Asia has been replaced by rubber plantations, there is very little information about the impact of such forest conversion on bat diversity. To address this deficiency, trapping and acoustic monitoring programmes were carried out in Ton Nga Chang and Khao Ban That wildlife sanctuaries in southern Thailand with the purpose of comparing species diversity and activity of understorey insectivorous bats at sites in forest and in nearby monoculture rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 58 publications
1
44
2
Order By: Relevance
“…Leaf‐gleaning bats are less abundant in agricultural systems than in natural forest (Phommexay et al . ) suggesting natural forests are sources of bats for nearby agroforests, but we did not find any evidence for forest distance‐dependent effects of bats.…”
Section: Discussioncontrasting
confidence: 78%
“…Leaf‐gleaning bats are less abundant in agricultural systems than in natural forest (Phommexay et al . ) suggesting natural forests are sources of bats for nearby agroforests, but we did not find any evidence for forest distance‐dependent effects of bats.…”
Section: Discussioncontrasting
confidence: 78%
“…Note, this is in contrast to studies in shade cocoa agroforests, which are structurally complex habitats, that have found these areas to support similar levels of bat species richness to forests (Harvey and Villalobos 2007). Given the insectivorous diet of most echolocating bats (Fenton 1982), monocultures, such as cacao plantations are likely to make poor habitats for Paleotropical bats (Fukuda et al 2009;Phommexay et al 2011). In addition, cacao plantations on Makira are relatively open habitats, which also poses an increased predation risk for bats (i.e.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to testing these hypotheses, our study supplements the limited literature for bat acoustics in the Paleotropics (Phommexay et al 2011) and provides the first acoustic characterizations and morphological data of bat species common and/or endemic for a data-deficient region of the Solomon Islands. Through this study we also document some of the challenges of using ultrasonic bat detection in a remote and poorly studied region, which are common features of many conservation priority areas; we hope this work will help guide future assessments in similar challenging regions.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Acoustic surveys could potentially contribute additional information concerning bat activity and the structure of bat assemblages in these habitats. The first insights from the Old World come from southern Thailand, where Phommexay et al (2011) sampled bats in forest and neighboring rubber plantations using bat detectors, mist nets, and harp traps. Although diversity and overall bat activity were much lower in plantations than in forests, differences between the two habitat types were not as severe as indicated by capture-based surveys.…”
Section: Tree Plantationsmentioning
confidence: 99%